The Middle to Later Stone Age transition in Eastern Africa (Ethiopia) - (:unkn) unknown (My University, 2013)
Modern humans are first associated in East Africa with technical behaviours defined as theMiddle Stone Age (MSA). The lithic technology is mainly characterised by flake production, as well as pointand elongated flake production, by means of Levallois and/or Discoïd methods, or prismatic core technology.One of the most representative tools is the retouched point. During the second part of the Upper Pleistocene,the production of elongated blanks (blades and bladelets) through prismatic cores becomes dominant and isassociated with microliths. This is defined as the Later Stone Age (LSA). However, the review of the UpperPleistocene sites from East Africa presents a more complex situation. Many lithic assemblages from this regionshow a mix of MSA and LSA features, leading to questions about the nature of changes between the Middleand the Later Stone Ages.Within the context of this question, the comparative study takes place between the assemblages of the sitesof Porc-Epic and Goda Buticha, located in south-eastern Ethiopia. The typo-technological analysis of the lithicmaterial relies on diagnostic criteria that appear to change through time : 1) the production of elongated blanks,2) the manufacture of retouched points, and 3) the manufacture of microliths. This study highlights the presenceof technical elements shared by both Pleistocene and Holocene layers. These elements could be interpreted interms of technical continuity, with a very gradual MSA/LSA transition. This technological pattern raises thequestion of the relevance of the use of the terminology MSA and LSA for this region. These results are of greatimportance with reference to major questions that are central to this period, namely the climatic instability,marked by very arid phases (the “Big Dry”) and the “Out of Africa 3” event. The lithic analyses of these two sitesconstitute
Keywords: African Research